La vulnérabilité d’un territoire, un héritage complexe à révéler : démonstration à travers l’étude géohistorique du risque d’inondation en Val d’Orléans (France) - Sylvain Dournel (Éditions en environnement VertigO, 2016)
The present paper focuses on the optimization of flood risk prevention policies in Val d’Orléans. On that plain and in the whole Val de Loire, the consciousness of flood risk is not shared for most inhabitants and not even for some local actors. Nevertheless an impressive defense plan against the river flood, called levees, erected at the 16th century, testifies the initial recurrence of floods. These embankments also had the effect to slow down the communications between the river and the valley, to confine the river bed and to make its access more complex. This is an issue because the levees have often proven their unefficiency during the main floods, yet unusual and irregular. However, lull periods have made people wrongly think that they could overpower the risk. The last lull since 1907 has come with a large urban sprawl in the western part of the Val d’Orléans, such that 48 000 people are exposed to major floods. In this complex situation, vulnerability is here treated as a legacy that should be not only revealed but also asserted in order to revive a memory and even a local culture of flood risk. This work gives importance to longer time and hence resorts to historical geography and to geohistory to determine the flood mechanisms and the constructions of vulnerability of the Val d’Orléans.